Continence care for people with dementia living at home in Europe: a review of literature with a focus on problems and challenges. Issue 3 (7th November 2016) - Gove, Dianne; Scerri, Anthony; Georges, Jean; van Houten, Paul; Huige, Nicole; Hayder‐Beichel, Daniela; Leichsenring, Kai; Morris, Vikky Christina
Abstract : Aims and objectives: To report the findings of a review of literature relating to the continence care of community‐dwelling people with dementia in Europe. Background: More than two‐thirds of people with dementia live at home, and many experience continence problems. Incontinence is a significant contributor towards institutionalisation. Care and support is often inadequate or inappropriate, and guidelines are lacking. This represents a failure to respect the human rights and dignity of this group. Design: A structured review of the literature relating to the continence care of community‐dwelling people with dementia in Europe with a focus on problems and challenges. Methods: Search terms reflecting dementia, continence, care/management and guidelines for community‐dwelling people with dementia were applied to four databases. Hand‐searching was also carried out. A total of 208 articles were searched for content relating to problems and challenges linked to continence care for this group. Results: Six relevant articles were fully reviewed. The main difficulties and challenges included the following: (1) perceptions, (2) availability/provision of support and care, (3) financial cost, (4) mobility and the environment, (5) relationships and social inclusion and (6) emotional issues. Conclusion: Dementia and incontinence have profound effects on quality of life. The dearth of good quality data within this area and the findings of the review confirm the need for expert, consensus‐based guidelines and appropriate research to ensure that the rights and dignity of people with dementia are respected. Relevance to clinical practice: The findings of the review will hopefully raise awareness amongst healthcare professionals in community practice of unmet needs of people with dementia and continence problems, and their caregivers, especially those related to social, financial, emotional and relational issues. The review does not provide solutions or guidance but is helpful in highlighting some of the key areas where special attention is needed.